Factors Influencing Quality of Life Among Infertile Women - Mahlegha Alami; Louiz Amanati; Sholeh Shokrabi; Hamid Haghani; Fatemeh Ramezanzadeh (Iran University of Medical Sciences, 2009)
Background and Aim : Fertility is highly valued in most cultures, and the desire to have a child is essential for human motivation. Studies have shown that infertility has negative effects on quality of life. However, recognition of factors influencing quality of life may be useful in planning to improve it. The aim of this study was to investigate quality of life and influential factors among infertile women.   Material and Method : This study had correlational design in which 3 types of questionnaires was used to collect data about demographic factors, quality of life and irrational parenthood cognitions of the participants. One hundred forty seven infertile women without known physical or psychological disorders, selected by continuous sampling method, filled out questionnaires.   Results : Regarding the findings, the quality of life of 48.3%, 36.1% and 15.6% of samples were good, fair and poor, respectively. Also, statistically meaningful relationship were found between quality of life and history of infertility treatment (P= 0.011), strength of desire to have child (P < 0.0001), previous pregnancy outcome (P=0.04), and irrational parenthood cognitions (P < 0.0001) .   Conclusion : Quality of life of infertile women could be affected by the irrational parenthood cognitions mostly. So, identifying this group would result in better management for allocation of appropriate counseling. The researchers suggest comparative study of quality of life between infertile and fertile women.